Regional illitization in bentonite beds from the East Slovak Basin based on isotopic characteristics (K-Ar, δ18O and δD) of illite-type nanoparticles. (April 2014) - Clauer, N.; Honty, M.; Fallick, A. E.; Šucha, V.; Aubert, A.
Abstract: Nanometre-sized illite-type crystals extracted from mixed-layer illite-smectite of cored bentonite beds from the East Slovak Basin were studied to investigate timing, duration and physical/chemical conditions of their nucleation and growth. The study includes application of the results to an evaluation of the regional extent of illitization. Close to salt-bearing formations, the nanometric particles underwent a more intense illitization, of identical duration, but with changing oxygen and hydrogen isotope characteristics of the parental brines. A comparison of the stratigraphic ages of the bentonite beds with the K-Ar ages of the authigenic crystals shows that illitization started during the Middle-Miocene Serravalian (Lower Sarmatian) subsidence that lasted from 17 to 11.5 Ma. Duration of illitization was bracketed between 14.5 and 9.0 Ma, with further episodes until recently at 0 Ma, depending on the geographic location of the host beds. The calculated subsidence rate varies from less than 300 m/Ma to more than 500 m/Ma and the thermal gradient ranges from 60°C/km to less than 50°C/km. The K-Ar ages of the nanometric illite point to either short-duration illitization when the onset was soon after sedimentation, or long-duration when the onset was significantly later after sedimentation. The illite δ 18 O varies little with increasing crystal size, whereas the δD changes significantly. In most samples the crystallization temperature determined by different criteria did not change significantly during crystal growth, but the oxygen and hydrogen isotopic compositions of the interacting fluids varied depending on sample location, immediate environment, timing and duration of illitization. The stable isotope composition of illite in bentonite beds with reduced fluid-rock ratios gives insight into the fluid-temperature regime of sedimentary basins through identifying local processes rather than wide-scale ones. Illitization is episodic with variable duration along different crystallization pathways, and to various extents in low-porosity, low-permeability bentonite beds. Depending on local conditions, illitization may vary even within apparently homogeneous beds. This contrasts with the situation for porous aquifers having large-scale fluid connectivity.